Charif Benhelima : Harlem on my mind - I was, I am - Benhelima, Charif; Harithas, James; Phillips, Caryl; Géo, Daniella; Galerie Michael Janssen, Berlin (Köln : Snoeck, 2011)
Black and white photography of ghetto life in Harlem from 1999-2002.
Catalog of an exhibition held at Galerie Michael Janssen, Berlin, from Feb. 4-March 5, 2011.
Text in English and German.
kunstcatalogus
Keywords: Benhelima, Charif; Harlem, New York